Literasi digital dan akhlak peserta didik dalam pembelajaran - Sasrita, Ira Dwi; Alwardah; Ali, Suryanis; Astuti BN, Aulia; Ernawati (Program Studi Magister Pendidikan Agama Islam, 2026)
This article aims to analyze the role of digital literacy in shaping students’ moral character within technology-based learning from the perspective of Islamic education. The study employs a qualitative descriptive approach through literature review and limited field research, including observations of digital learning activities and semi-structured interviews with elementary school teachers and students. Data were analyzed using thematic analysis to identify the relationship between digital literacy practices and the internalization of moral values. The findings indicate that digital literacy integrated with Islamic moral values positively contributes to the development of students’ honesty, responsibility, discipline, and ethical communication in digital spaces. Conversely, digital learning that focuses solely on technical skills tends to increase the risk of moral degradation, such as plagiarism and poor digital ethics. These results emphasize that digital literacy cannot be separated from moral education and should be systematically integrated into the learning process. This article offers a conceptual contribution by strengthening the paradigm of morality-based digital literacy that is relevant to the development of Islamic educational practices in the digital era. Abstrak Artikel ini bertujuan menganalisis peran literasi digital dalam pembentukan akhlak peserta didik pada pembelajaran berbasis teknologi dalam perspektif pendidikan Islam. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui studi literatur dan studi lapangan terbatas berupa observasi pembelajaran digital serta wawancara dengan guru dan peserta didik sekolah dasar. Data dianalisis menggunakan analisis tematik untuk mengidentifikasi keterkaitan antara praktik literasi digital dan internalisasi nilai-nilai akhlak. Hasil penelitian menunjukkan bahwa literasi digital yang diintegrasikan dengan nilai akhlak Islam berkontribusi positif terhadap pembentukan sikap jujur, tanggung jawab, disiplin, serta etika komunikasi peserta didik di ruang digital. Sebaliknya, pembelajaran digital yang hanya berorientasi pada aspek teknis berpotensi memunculkan degradasi moral seperti plagiarisme dan rendahnya etika bermedia. Temuan ini menegaskan bahwa literasi digital tidak dapat dipisahkan dari pendidikan akhlak, dan keduanya perlu diintegrasikan secara sistematis dalam pembelajaran. Artikel ini memberikan kontribusi konseptual berupa penguatan paradigma literasi digital berbasis akhlak yang relevan bagi pengembangan praktik pendidikan Islam di era digital.